Pengembangan Kemampuan Soft-Skills dalam Pembelajaran Bahasa Inggris Melalui Project-Based Learning - Nurwidasa, Pius (Jurnal Orientasi Baru, 2008)
An integral skill-building is a real challenge within the world of education. To meet the challenge, a student-based methodology of learning or a project-based Learning needs to be developed. This methodology will greatly benefit each student while involving each of them in building what is called human knowledge. Within this regard, the development of the so-called soft-skills is expected to happen excellently. A Project-based Learning is applicable even for the program of english as the second language. With this approach, each student is expected to be able to experience the development of his or her intellectual ability, to learn to work in a team, to solve problems in dialogue, as well as learning to live with others.